Effects of exercise intensity on lymphocyte H2O2 production and antioxidant defences in soccer players. Issue 3 (10th December 2007) - Sureda, A; Ferrer, M D; Tauler, P; Romaguera, D; Drobnic, F; Pujol, P; Tur, J A; Pons, A
Abstract : Objective: Physical exercise is capable of enhancing or suppressing the immune response depending on the intensity and duration of exercise. This study investigated how exercise intensity influences the lymphocyte antioxidant response and the induction of cellular oxidative damage. Design: Eighteen voluntary male pre-professional soccer players participated in this study. Sportsmen played a 60 min training match, and were divided into three groups depending on the intensity degree during the match: low, medium and high intensities. Measurements: Malondialdehyde (MDA), vitamins C and E and haem oxygenase-1 (HO-1) gene expression were measured in lymphocytes. Reactive oxygen species (ROS) production was determined in lymphocytes and neutrophils. Results: Lymphocyte MDA levels and H2 O2 production were significantly increased in the group which performed the most intense exercise. Neutrophil counts and ROS production increased progressively with the exercise intensity. Vitamin C significantly decreased after exercise in the highest-intensity group in comparison with initial values, whereas vitamin E levels significantly increased in the medium and high-intensity groups. HO-1 gene expression significantly increased in the medium and high-intensity groups. Conclusions: Exercise intensity affects the lymphocyte and neutrophil oxidant/antioxidant balance, but only exercise of high intensity induces lymphocyte oxidative damage.